RETURN ON ASSET, DEBT TO EQUITY RATIO, PRICE EARNING RATIO, KURS DAN INFLASI TERHADAP HARGA SAHAM - Rina Ani Sapariyah; Yenni Khristiana; Juwanto Juwanto (ADVANCE, 2017)
The Empirical purpose in this study are influence determined significant Return On Asset (ROA) variable, Debt to Equity Ratio (DER), Price Earning Ratio (PER), Inflation and a rate of exchange about Price stock. The Population in this study all commercial banks in Indonesia are listed on the Stock Exchange. The Sample in this study 10 commercial banks company are listed on the Stock Exchange period 2012-2016. The Sample in this study used purposive sampling method, criteria by commercial bank company who have totally asset more than 100 triliun during monitoring periods. The study used analisis test such as classic assumption test, multiple linier regression analysis and hypothesis test. The classic assumption test showed data in this study are normal distribution, did not happen multikolinieritas, autokorelation and heterokesdesitas. The study multiple liniar regression showed ROA, DER, Inflation and a rate of exchange variable positive and significant impact on the price stock, PER showed positive but not significant on the price stock. The t test showed that ROA,DER, Inflation and a rate of exchange variable possitif significant effect on the price stock, PER variable possitive not significant on the price stock and inflation variable negative significant effect on the price stock.Keywords: Return On Asset, Debt to Equity Ratio, Price Earning Ratio, Kurs, Inflasi, Harga Saham